Inhibition of parametric decay in heating microwave beams during fluctuations of the density profile in the edge island of Wendelstein 7-X. (1st January 2023) - Tancetti, A; Nielsen, S K; Rasmussen, J; Moseev, D; Stange, T; Marsen, S; Vecséi, M; Killer, C; Wurden, G A; Jensen, T; Stejner, M; Anda, G; et al.
Abstract: Experimental evidence of parametric decay instability (PDI) is observed in the Wendelstein 7-X stellarator, when high-power microwave beams cross a stationary magnetic island at the plasma edge. Here, trapping and build-up of upper hybrid waves within a density bump (measured within the island by alkali beam emission spectroscopy) is responsible for the reduction of the instability power threshold below the maximum gyrotron power. In this paper, we provide the first experimental evidence of the connection between the trapping mechanism in the island density bump and excitation of PDI-related signals. We show correlations of periodic crashes in the PDI-related signals with quasi-continuous fluctuations at the plasma edge, which, additionally, cause a flattening of the density profile in the island. We demonstrate that flattening of the experimental density profiles can suppress the trapping mechanism and inhibit the low-threshold PDI. PDI on the edge island could alter the power deposition profile and reduce the efficiency of the electron cyclotron resonance heating system, simultaneously posing a serious threat to the optimal operation of microwave-based diagnostics and plasma-facing components.